Arterial stiffness in patients with localized and generalized severe chronic periodontitis: A preliminary study - Arief, Erry Mochamad; Khee, Ho Ting; Rehman, Asia; Hassan, Akram; Khamis, Mohd. Fadhli (Padjadjaran Journal of Dentistry, 2009)
A relationship between periodontal disease and cardiovascular disease (CVD) has been reported in several studies. This association was explained based on the chronic systemic inflammatory response which may lead to arterial stiffness in chronic periodontitis (CP). To compare arterial stiffness as carotid-femoral pulse wave velocity (PWV) between patients with localized severe CP (LSCP) and generalized severe CP (GSCP). Five patients with LSCP and 12 patients with GSCP were recruited in a cross-sectional study. Subjects were excluded if they had systemic diseases other than CP. Diagnosis of LSCP and GSCP was made based on probing depth and radiographic bone loss. Carotid-femoral PWV was measured using the Complior® machine. Data were analyzed using SPSS. Carotid-femoral PWV was higher among patients with GSCP as compared to those with LSCP although the difference did not reach a significant level. Median (interquartile range) PWV was 7.5 (1.50) and 7.0 (1.03) m/sec respectively in patients with GSCP and LSCP (p = 0.224). Among patients with CP, aorta is stiffer in GSCP than in LSCP